Development of a GA-Fuzzy-Immune PID Controller with Incomplete Derivation for Robot Dexterous Hand - Xin-hua Liu; Xiao-hu Chen; Xian-hua Zheng; Sheng-peng Li; Zhong-bin Wang (The Scientific World Journal)
In order to improve the performance of robot dexterous hand, a controller based on GA-fuzzy-immune PID was designed. The control system of a robot dexterous hand and mathematical model of an index finger were presented. Moreover, immune mechanism was applied to the controller design and an improved approach through integration of GA and fuzzy inference was proposed to realize parameters’ optimization. Finally, a simulation example was provided and the designed controller was proved ideal.